Evaluation of Selected Varieties of a cotton in the Conditions of Fuzzy Initial Information - B.T, Solieva; M.D, Sotvoldiev; A, Kxudayberganov (International Journal of Engineering and Technology, 2018)
One of the applied problems of decision-making under conditions of uncertainty, called tasks of making weakly structured decisions, is considered. The essence of this task is to choose the most acceptable variety of cotton from a given set of crops, providing optimal values for agrotechnological parameters (yield, length and strength of fiber, oil content, etc.) in different initial conditions: sowing, cultivation, growing and harvesting. The initial conditions are of a non-quantitative, incomplete, linguistic nature (collectively referred to as fuzzy source information) and are represented in the form of logically interconnected linguistic expressions.Â Â
Keywords: Decision-making; uncertainty; agrotechnological parameters; membership functions; selection varieties.